Hetero-grafting affects flavonoid biosynthesis in sweet orange 'Newhall' (Citrus sinensis) peels: a metabolomics and transcriptomics analysis - Li, Qin; Yao, Junfei; Zheng, Wei; Wang, Jialu; Liao, Ling; Sun, Guochao; Wang, Xun; Deng, Honghong; Zhang, Mingfei; Wang, Zhihui; Xiong, Bo (Frontiers in Plant Science, 2023)
Citrus cultivation involves the widespread practice of grafting, which has a significant impact on citrus development and fruit quality and yield. However, understanding the effect of flavonoid compounds after different rootstock grafting have been limited. Flavonoid compounds, found at the highest levels in citrus peels, contribute to improving fruit quality and nutritional value. In this study, scion-rootstock interaction was investigated at various developmental stages when sweet orange 'Newhall' was hetero-grafted with two commonly used rootstocks (Poncirus trifoliate population, C. junos Siebold ex Tanaka). Physiological index detection showed a higher concentration of total flavonoid content in peels of sweet orange 'Newhall' grafted on Poncirus trifoliate population (ct) than C. junos Siebold ex Tanaka (cj). Further metabolomic analysis identified 703 flavonoid compounds, including flavones, flavonols, and flavanones. Out of the 25 flavonoids affected by different rootstock grafting and developmental stages, most were flavones.Transcriptomic analysis identified 8,562 differentially expressed genes (DEGs). Co-expression and Pearson's correlation analysis discovered six hub structure genes and 19 transcription factors (TFs) that affected flavonoid biosynthesis. In addition to increasing the transcript levels of genes that synthesize flavones, flavonols, and flavanones, the scion-rootstock interaction also affected the expression of many TFs. Taken together, our findings suggested that hetero-grafting could promote the accumulation of flavonoid compounds in citrus peels during the development stages.These results offered fresh perspectives on grafting's application usefulness and the enhancement of the accumulation of nutritive flavonoid components by grafting in citrus.